Kajian Sistem Tanam Usaha Tani Padi Gogo di Lahan Kering Kabupaten Boyolali, Jawa Tengah - Dewi Sahara; Ekaningtyas Kushartanti (Jurnal Ilmu Pertanian Indonesia, 2019)
This study aimed to determine the feasibility of upland rice farming, the breakeven point of price and production, and the ratio of increasing profit of the jajar wayang to double row planting system. The study was conducted in Singosari Village, Mojosongo Sub-District, Boyolali District during rainy season in 2016/2017. The study of upland rice planting system was demonstrated on 4 ha of dry land, using Inpago 8 and Inpago 9 varieties which were planted in double row and jajar wayang system. The data were analyzed descriptively both qualitatively and quantitatively. The results of the analysis showed that the Inpago 9 variety grown in double row gave the highest productivity (5.5 tons/ha) compared to the Inpago 8 variety and the other cropping systems so that the profit obtained was IDR13.552.000/ha (RCR=2.99). Break even point analysis of prices and production showed that if there was a decrease in prices and production of 57.39-66.59%, the farmers did not suffer losses. Changes in the planting system from jajar wayang to double row provided a proportion of increase in profits in Inpago 8 varieties by 18.79% and in Inpago 9 varieties by 7.71%, indicating NKB value of 1.24 and 1.09. Therefore, the productivity of upland rice on dry land can be increased with double row planting system.